The impact of housing expenditure on the incidence and severity of poverty in New Zealand - Stephens, Bob (School of Management Working Papers, 1994)
This paper represents a small part of a much larger project looking at the incidence and severity of poverty in New Zealand both for 1993, and for trends in poverty between 1984 and 1993. Eight interrelated measures of poverty have been developed, designed to show the level or incidence of poverty, who is poor as shown by a variety of different household characteristics, and the depth or severity of their poverty. Poverty measures can also be shown by tenure of dwelling and status of lanqlord, as well as before and after housing costs. When a time trend is taken, the data can provide a measure of the impact of policy change on poverty.